Helix Light Vortex Theory (HLV) - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
This paper introduces a novel hypothesis for the origin of electric charge, moving beyond the axiomatic treatment within the Standard Model. Within the Helix-Light-Vortex (HLV) framework, we propose that electric charge is not a static, intrinsic property but an emergent dynamical phenomenon. The hypothesis posits that charge arises from a directed, coherent flow of information from a universal Information Field (Φ) that actively drives the phase evolution of a particle's underlying matter field (Ψ). This mechanism is grounded in a specific coupling term previously established in the HLV Lagrangian. This relationship is formalized by proposing a direct proportionality between the conserved charge current (J^μ) and the gradient of the information field (∂^μΦ). As a key consequence, we extend the standard Maxwell's equations to include this information flux as a new source term for the electromagnetic field. This new framework is not merely conceptual; it yields several falsifiable predictions, including potential micro-variations of the elementary charge in extreme environments, distinct high-frequency signatures from the information field during pair production, and a potential weak coupling of consciousness to charge phenomena. Ultimately, this work reinterprets charge as a consequence of informational flux, offering a new perspective that unifies concepts from field theory and information theory.
This paper introduces a novel hypothesis for the origin of electric charge, moving beyond the axiomatic treatment within the Standard Model. Within the Helix-Light-Vortex (HLV) framework, we propose that electric charge is not a static, intrinsic property but an emergent dynamical phenomenon. The hypothesis posits that charge arises from a directed, coherent flow of information from a universal Information Field (Φ) that actively drives the phase evolution of a particle's underlying matter field (Ψ). This mechanism is grounded in a specific coupling term previously established in the HLV Lagrangian. This relationship is formalized by proposing a direct proportionality between the conserved charge current (J^μ) and the gradient of the information field (∂^μΦ). As a key consequence, we extend the standard Maxwell's equations to include this information flux as a new source term for the electromagnetic field. This new framework is not merely conceptual; it yields several falsifiable predictions, including potential micro-variations of the elementary charge in extreme environments, distinct high-frequency signatures from the information field during pair production, and a potential weak coupling of consciousness to charge phenomena. Ultimately, this work reinterprets charge as a consequence of informational flux, offering a new perspective that unifies concepts from field theory and information theory.